EXPERIMENTAL STUDY ON NON SPORULATING ESCHERICHIA COLI BACTERIA IN REMOVING METHYLENE BLUE - BANDARY BALRAJ,; ZAKIR HUSSAIN,; PULIPATI KING, (International Journal of Pharma and Bio Sciences, 2016)
World is ever witnessing the fashion revolution and youth passion, always lies in adopting and updating themselves with the recent trends and developments. Therefore, it creates a need for well designed and colorful clothing requirements day by day. Increasing the demand for clothing and simultaneous increase in production activities, largely responsible for the textile dye waste. In the present work methylene blue is biodegraded using Escherichia Coli to study the parameters influencing the dye degradation mechanism such as contact time, initial concentration of dye, pH of the solution, temperature, inoculum volume, and carbon and nitrogen sources. Dye degradation percentage of up to 89.52 has been achieved in 4 hrs of optimum contact time. Best results were observed at the temperature of 37oC. Degradation percentage shoots up to 92.9% with an increase in inoculum volume to 8 ml. Glucose and ammonium sulphate are proven to be the best carbon and nitrogen sources respectively.